School convivencia: Reviewing the concept - Cecilia Fierro-Evans; Académica e Investigadora de la Universidad Iberoamericana León; Patricia Carbajal-Padilla; Investigadora (Escuela de Psicología, Pontificia Universidad Católica de Valparaíso, 2019)
This article reports an effort to review the concept of school convivencia (peaceful coexistence, living together) in the Spanish context with the purpose of advancing into its clarification, and thus contributing to developing a common language in the Latin American region. The authors conduct a basic literature review oriented to identify the main theoretical approaches in the convivencia field. Subsequently, they analyze four studies focused on systematizing the prevailing approaches in the study of school convivencia. As a result, they propose a concept of convivencia from a social justice perspective adapted to education, and they operationalize it in three areas of school life: pedagogical-curricular, organizational-administrative, and socio-communitarian. This comprehensive notion of school convivencia may guide future research, educational initiatives, and school assessments in the convivencia field that may respond to the violence and pervasive social exclusion that exist in the Latin American region.